Simeon the Righteous in rabbinic literature : a legend reinvented - Tropper, Amram D. (Ancient Judaism and Early Christianity, 2013)
In Simeon the Righteous in Rabbinic Literature: A Legend Reinvented , Amram Tropper investigates the rabbinic traditions about Simeon the Righteous, a renowned Jewish leader of Second Temple times. Tropper not only interprets these traditions from a literary perspective but also deploys a relatively new critical approach towards rabbinic literature with which he explores the formation history of the traditions. With the help of this approach, Tropper seeks to uncover the literary and cultural matrices, both rabbinic and Graeco-Roman, which supplied the raw materials and literary inspiration to the rabbinic authors and editors of the traditions. Tropper's analysis reveals that in reinventing the legend of Simeon the Righteous, the rabbis constructed the Second Temple past in the image of their own present.